موانع اعتبار مفهوم المخالفة - الغامدي، ياسر بن درويش بن غرم الله آل محفوظ (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2020)
بسم الله الرحمن الرحيم الحمد لله وحده، والصلاة على من لا نبي بعده: هذا البحث يتطرق إلى موانع اعتبار مفهوم المخالفة عند القائلين به وقد احتوى على مقدمة ومبحثين وفهارس للبحث. وقد خصص المبحث الأول: لتعريف مفهوم المخالفة، وإطلاقاته، وتحرير محل النزاع في حجيته، ومذاهب العلماء وأدلتهم؛ وفيه خمسة مطالب. أما المبحث الثاني فقد خصص: لموانع اعتبار الموافقة عند القائلين به؛ وفيه ثمانية مطالب. ثم فهارس البحث: فهرس المصادر والمراجع - وفهرس المحتويات. والحمد لله كما ينبغي لجلال وجهه وعظيم سلطانه، وأسأله الهدى والسداد، وصلى الله وسلم على نبينا محمد وعلى آله وصحبه وسلم.
In the name of Allah the most Passionate the most Merciful Praise be to Allah and prayers be upon the Messenger of Allah: This research is related to investigating the preventions from considering concept of MOKHLAFAH among those scholars who acknowledge the concept. It includes an introduction, two research topics and the indexes. The first topic is devoted to defining the concept of MOKHLAFAH and what it is related to. It also present the scholars argument about its consideration and their methodology and evidence of the concept. This topic has five research subjects. The second topic is devoted to illustrating the preventions from considering the concept of MOWAFAQAH among the scholars who acknowledge it. It has eight research subjects. Then the indexes are presented: index of sources, references, and content index Researcher in charge of the thesis Dean of the Faculty of Sharia and Islamic Studies.
Keywords: الفقه الإسلامي -- أصول الفقه -- المذاهب الفقهية -- تحرير محل النزاع